Production and emission evaluation of neem biodiesel blends in a single cylinder diesel engine. (2022) - Mathiyazhagan, M.; Meenakshi Sundaram, K.; Bupesh, G.
Abstract: Biodiesel made from edible and non-edible vegetable oils, waste cooking oils, and animal fats is gaining popularity these days due to its renewable nature and environmental friendliness. As a result, several nations are switching to biodiesel production from plant oils such as maize, soy bean, canola, sunflower, palm, and others. However, these oils are out of reach for developing nations like India, since they may result in a lack of food-grade oil as well as a significant increase in gasoline prices. In this study, we used domestic non-edible neem oil to produce biodiesel, and to determine the best biodiesel blend for future fuel without compromising air quality. Using an Acid and Base catalyst, unprocessed neem oil with a high FFA (Free Fatty Acid) content was successfully transformed into pure biodiesel. As a result, according to this study, using 20% neem biodiesel will reduce the consumption of petroleum diesel while having no negative impact on the environment.